Oral midazolam for conscious sedation of children during minor procedures. Issue 4 (July 1998) - Davies, F C; Waters, M
Abstract : OBJECTIVE: To compare the safety and efficacy of two doses of oral midazolam, and to assess the drug induced amnesia obtained, when used for conscious sedation of children undergoing minor procedures in the accident and emergency (A&E) setting. METHODS: A two stage trial was completed: an initial prospective, double blinded, randomised trial comparing 0.2 mg/kg midazolam suspension with 0.5 mg/kg, followed by further data collection on the higher dose. Children whom staff and parents felt required sedation for accurate and humane completion of minor procedures were selected. Anxiety was measured using physiological parameters, a behavioural anxiety score, a parental visual analogue scale, and a telephone questionnaire at 2-7 days after the procedure. RESULTS: Fifty patients in total were recruited. Randomisation between two doses ceased after 20 patients since staff, despite being "blinded", perceived there to be a wide variation in response to midazolam and attributed that to the difference in doses. On breaking the code these suspicions were partly supported. Due to reluctance to continue with the lower dose all children subsequently received 0.5 mg/kg. At this higher dose oral midazolam had an onset of action of 15 minutes and was effective in 76% of children (as measured by anxiety score and/or subsequent amnesia). Amnesia was reported in 66% of children. There were no adverse side effects except paradoxical hyperagitation in three (6%); this did not require any specific treatment. General anaesthesia was avoided in at least eight children in whom the procedure would not have been attempted without midazolam. Altogether 90% of parents said they would like it to be used again should similar circumstances arise. CONCLUSIONS: At 0.5 mg/kg oral midazolam appears safe and is effective in sedating most children for minor procedures. Its use should be considered by all A&E departments dealing with children.